STRATEGI STRATEGI MEMBANGUN KECERDASAN SOSIAL ANAK SEKOLAH DASAR MELALUI PEMBIASAAN TOLONG, MAAF DAN TERIMA KASIH - belik, ridwan luis (Jurnal Ilmiah Ibtida, 2025)
The importance of this social intelligence not only has an impact on relationships between peers but also affects children's learning ability and personal development. The purpose of this study is to find out the implementation of the Please, sorry, and Thank You habituation in SD 04 Beluk. This research uses a qualitative approach which is an approach that explains social reality in depth in the form of abstractions, words, and statements. This research was conducted at SD 04 Beluk located in Beluk Village, Belik District, Pemalang Regency in October 2024. The subjects of this study are students in grade 05 SD 04 Beluk which totals 29 students and 1 class teacher. SD 04 Beluk itself helps students build their social intelligence through the implementation of the Please, sorry, and Thank You program at 04 Beluk Elementary School. Research Results. That children's social intelligence can be developed through various factors that interact with each other. Individual factors such as empathy, self-awareness, effective communication, social experiences, and emotional control. Family factors are particularly influential, where good communication, emotional support, teaching of social values, and active involvement of parents in a child's activities help strengthen social intelligence. Environmental factors such as a supportive school environment, extracurricular activities, an inclusive community environment, and access to public facilities provide children with opportunities to interact and develop their social skills.